The ghost prison - Delaney, Joseph, 1945- (Sourcebooks Fire, 2013)
On his first night as a prison guard, fifteen-year-old Billy investigates the forbidden prisoner kept down in the Witch Well. Even though he has been told to stay away, Billy can't help but have a look, and soon discovers why this prisoner is considered so dangerous.